ZMO target material and preparation method thereof
By adding doped metal oxides to zinc oxide materials, the relative density and carrier migration ability of the target material are improved, and the problem of high resistivity of zinc oxide targets in the prior art is solved, and the effect of high density and low resistance is achieved.
Patent Information
- Application Number
- CN202411763519.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art is difficult to provide zinc oxide magnesium targets with high density and low resistance.
By adding doped metal oxides, such as tantalum pentoxide, ceria, titanium dioxide, etc. to zinc oxide materials, the relative density and carrier migration ability of the target material are improved, thereby reducing the resistivity.
The relative density and carrier migration ability of zinc oxide magnesium targets are achieved, the resistivity of the target is reduced, and the goal of high density and low resistance is achieved.
Smart Images

Figure BDA0005168279210000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrically permeable thin film production, and in particular to a ZMO target material and a preparation method thereof. Background Art
[0002] Zinc oxide is an environmentally friendly, abundant, multifunctional wide-bandgap oxide photoelectric material. After degenerate doping with a certain amount of trivalent elements (such as Al, Ga, B, etc.), it can become a transparent conductive oxide material (transparent conductive oxide, TCO) with higher photoelectric performance. It has the advantages of ultraviolet light absorption, visible light transparency, infrared light reflection and adjustable electrical properties. It is increasingly used in optoelectronic information fields such as flat panel displays, thin-film solar cells, Low-E glass for building energy conservation, smart glass, etc.
[0003] In addition, after doping zinc oxide with MgO material with a wider bandgap, zinc oxide material is given some new characteristics and applications. 2+ The ionic radius (0.072nm) and Zn 2+ The ionic radius of Mg is close to that of Mg (0.074 nm). 2+ Substitution Zn 2+ It will not cause large lattice distortion, and it is easy to form Mg x Zn 1-x O ternary alloy, related research shows that this Mg x Zn 1-x The band gap and structural characteristics of the O film depend on the Mg content x in the alloy film. The band gap of ZnO is 3.37eV, and the band gap of MgO is 7.8eV. Theoretically, with the change of Mg content, the prepared MgO x Zn 1-x The bandgap width of the O film varies from 3.37 to 7.8 eV. This wider bandgap MgZnO film has important applications in high-performance thin film transistor devices (TFT), ultraviolet detectors, and Cd-free high-resistance layers of new structure CIGS thin film solar cells.
[0004] Chinese patent application 200710160242.7 discloses that the transparent conductive film is a gallium-doped or aluminum-doped zinc-magnesium-oxide film, and the molar percentage content of each component is: aluminum or gallium 1.0-5.0%, magnesium 1-20.0%, and the balance is zinc, and the molar ratio of (Zn+Mg+Al) or (Zn+Mg+Ga) to 0 is 1:1.
[0005] This scheme adopts DC reactive magnetron sputtering method, with zinc-magnesium-aluminum or zinc-magnesium-gallium alloy as the target material. This scheme is simple, the doping amount is easy to control, the deposition system is simple and easy to operate, and large-area coating can be achieved. Compared with other preparation technologies, it is more conducive to industrial production. The prepared gallium-doped zinc-magnesium-oxygen and aluminum-doped zinc-magnesium-oxygen transparent conductive films have high transmittance, good electro-optical properties, repeatability and stability;
[0006] Further observation of this scheme shows that the doping element in this scheme is aluminum or gallium.
[0007] Chinese patent application 202210475550.3 discloses a zinc-magnesium oxide target material and a preparation method, which belongs to the field of semiconductor optoelectronic materials, magnetron sputtering coating and powder metallurgy sintering technology.
[0008] The method comprises the following steps: taking ZnO and MgO powder raw materials respectively according to the design group; processing the powder raw materials by adopting processes such as segmented ball milling, wet blanking, segmented degreasing, segmented sintering, machining, grinding, etc.; according to the method proposed in the scheme, a finished zinc-magnesium oxide target material with high density, guaranteed purity, no defects, uniform and fine grains, and not easy to crack can be obtained.
[0009] However, further observation of this scheme shows that this scheme pays more attention to the mechanical properties of the target material itself and does not dope other metal oxides into the target material.
[0010] The problem to be solved by this solution is: how to provide a zinc-magnesium oxide target material with high density and low resistance that is different from the prior art. Summary of the invention
[0011] The purpose of the present application is to provide a zinc magnesium oxide (ZMO) target material, which, on the one hand, improves the relative density of the target material by adding doped metal oxides, and on the other hand, provides the target material with a higher carrier concentration or a better carrier migration ability by doping metal oxides, thereby reducing the resistivity of the target material.
[0012] To achieve the above-mentioned purpose, the present application discloses a ZMO target material, which is made of zinc oxide, magnesium oxide, and doped metal oxide;
[0013] The doped metal oxide is selected from at least one of tantalum pentoxide, cerium dioxide, titanium dioxide, niobium pentoxide, manganese trioxide, and chromium trioxide;
[0014] The mass ratio of metal elements in zinc oxide and magnesium oxide is 73-91:9-27;
[0015] The metal element in the doped metal oxide is 1000 to 10000 ppm of the total mass of the metal elements in the ZMO target.
[0016] Preferably, the doped metal oxide comprises at least tantalum pentoxide.
[0017] Preferably, the doped metal oxide is a mixture of tantalum pentoxide and manganese trioxide, and the mass ratio of tantalum pentoxide to manganese trioxide is 1:1.
[0018] In addition, the present application also discloses a method for preparing the above-mentioned ZMO target material, comprising the following steps:
[0019] Step 1: Mixing zinc oxide powder, magnesium oxide powder and doped metal oxide powder with pure water to obtain a slurry;
[0020] Step 2: The slurry prepared in step 1 is spray granulated, cold isostatically pressed, vacuum hot pressed, and sintered to obtain a ZMO target.
[0021] Preferably, step 1 specifically comprises: mixing zinc oxide powder, magnesium oxide powder and doped metal oxide powder with a dispersant, a binder and pure water to obtain a slurry;
[0022] The amount of dispersant added is 1-3% of the total mass of zinc oxide powder and magnesium oxide powder;
[0023] The amount of binder added is 1 to 3% of the total mass of zinc oxide powder and magnesium oxide powder;
[0024] The dispersant is selected from any one of polyvinyl pyrrolidone and polycarboxylic acid;
[0025] The binder is selected from any one of polyvinyl alcohol, carboxymethyl cellulose, polyacrylamide, polyacrylic acid salt and polyethylene glycol.
[0026] Preferably, step 2 includes the following sub-steps:
[0027] Step A1: spray granulating the slurry obtained in step 1 to obtain a powder, and then cold isostatically pressing the powder at a pressure of 250 to 350 MPa for 3 to 8 minutes to obtain an intermediate;
[0028] Step A2: placing the intermediate obtained in step A1 in an environment with a vacuum degree of less than or equal to 10 Pa and performing vacuum hot pressing to obtain a ZMO green body;
[0029] Step A3: sintering the ZMO green blank obtained in step A2 in an air atmosphere to obtain a ZMO target.
[0030] Preferably, vacuum hot pressing is specifically as follows: in an environment where the degree of vacuum is less than or equal to 10 Pa, the temperature is increased to 400-600° C. at a heating rate of 0.4-1° C. / min and then heat preservation is started. After heat preservation for 10-30 minutes, pressurization is started, and the pressure is pressurized to 10-40 MPa and then heat and pressure are maintained for 120-360 minutes. After the heat preservation and pressure maintenance are completed, the temperature is lowered to room temperature and the pressure is lowered to normal pressure to complete the vacuum hot pressing.
[0031] Preferably, in an air atmosphere, the temperature is first increased to 400-600°C at a heating rate of 1.0-2.0°C / min, then increased to 1050-1150°C at a heating rate of 0.5-1°C / min, and then increased to 1300-1450°C at a heating rate of 0.8-1.5°C / min, and kept warm for 6-10 hours. Finally, the temperature is cooled to room temperature at a cooling rate of 1-2°C / min to complete sintering and obtain a ZMO target.
[0032] The beneficial effects of this application are:
[0033] The present application adds doped metal oxides to materials based on magnesium oxide and zinc oxide. The addition of the doped metal oxides not only improves the relative density of the target material, but also provides the target material with a higher carrier concentration or a better carrier migration ability by doping the metal oxides, thereby reducing the resistivity of the target material. DETAILED DESCRIPTION
[0034] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. In the description of the present invention, it should be noted that, if no specific conditions are specified in the embodiments, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0035] Example 1
[0036] Step 1: weigh zinc oxide powder and magnesium oxide powder in a mass ratio of zinc to magnesium of 85:15, and mix them with tantalum pentoxide powder, a dispersant, a binder, and pure water to obtain a slurry with a solid content of 65%;
[0037] The mass of tantalum in tantalum pentoxide powder is 6000ppm of the total mass of zinc, magnesium and tantalum;
[0038] The dispersant is polyvinyl pyrrolidone, and its addition amount is 2% of the total mass of zinc oxide powder and magnesium oxide powder;
[0039] The binder is polyvinyl alcohol, and its addition amount is 2% of the total mass of zinc oxide powder and magnesium oxide powder;
[0040] Step 2:
[0041] Step A1: spray granulating the slurry obtained in step 1 to obtain a powder, and then cold isostatically pressing the powder at a pressure of 300 MPa for 5 minutes to obtain an intermediate;
[0042] Step A2: in an environment with a vacuum degree of 8.5 Pa, the temperature is raised to 500° C. at a heating rate of 0.7° C. / min and then kept warm. After keeping warm for 20 minutes, pressurization is started and the pressure is increased to 25 MPa, followed by keeping warm and pressurization for 240 minutes. After the end of the keeping warm and pressurization, the temperature is lowered to room temperature and the pressure is lowered to normal pressure to complete vacuum hot pressing to obtain a ZMO green billet;
[0043] Step A3: Place the ZMO blank obtained in step A2 in an air atmosphere, first heat it to 500°C at a heating rate of 1.5°C / min, then heat it to 1100°C at a heating rate of 0.8°C / min, and then heat it to 1380°C at a heating rate of 1.2°C / min, keep it warm for 8h, and finally cool it to room temperature at a cooling rate of 1.5°C / min to complete sintering and obtain a ZMO target.
[0044] Example 2
[0045] Step 1: weigh zinc oxide powder and magnesium oxide powder according to a mass ratio of zinc to magnesium of 73:27, and mix them with tantalum pentoxide powder, a dispersant, a binder, and pure water to obtain a slurry with a solid content of 65%;
[0046] The mass of tantalum in tantalum pentoxide powder is 1000ppm of the total mass of zinc, magnesium and tantalum;
[0047] The dispersant is polyvinyl pyrrolidone, and its addition amount is 1% of the total mass of zinc oxide powder and magnesium oxide powder;
[0048] The binder is polyvinyl alcohol, and its addition amount is 1% of the total mass of zinc oxide powder and magnesium oxide powder;
[0049] Step 2:
[0050] Step A1: spray granulating the slurry obtained in step 1 to obtain a powder, and then cold isostatically pressing the powder at a pressure of 250 MPa for 8 minutes to obtain an intermediate;
[0051] Step A2: in an environment with a vacuum degree of 8.2 Pa, the temperature is raised to 400° C. at a heating rate of 0.4° C. / min and then the temperature is kept. After keeping the temperature for 30 minutes, pressurization is started and the pressure is increased to 10 MPa and then kept at this temperature for 360 minutes. After the heat preservation and pressure holding is completed, the temperature is lowered to room temperature and the pressure is lowered to normal pressure to complete vacuum hot pressing to obtain a ZMO green billet;
[0052] Step A3: Place the ZMO blank obtained in step A2 in an air atmosphere, first heat it to 400°C at a heating rate of 1.0°C / min, then heat it to 1050°C at a heating rate of 0.5°C / min, and then heat it to 1300°C at a heating rate of 0.8°C / min, keep it warm for 10 hours, and finally cool it to room temperature at a cooling rate of 1°C / min to complete sintering and obtain a ZMO target.
[0053] Example 3
[0054] Step 1: weigh zinc oxide powder and magnesium oxide powder in a mass ratio of zinc to magnesium of 91:9, and mix them with tantalum pentoxide powder, a dispersant, a binder, and pure water to obtain a slurry with a solid content of 65%;
[0055] The mass of tantalum in tantalum pentoxide powder is 10000ppm of the total mass of zinc, magnesium and tantalum;
[0056] The dispersant is polyvinyl pyrrolidone, and its addition amount is 3% of the total mass of zinc oxide powder and magnesium oxide powder;
[0057] The binder is polyvinyl alcohol, and its addition amount is 3% of the total weight of zinc oxide powder and magnesium oxide powder;
[0058] Step 2:
[0059] Step A1: spray granulating the slurry obtained in step 1 to obtain a powder, and then cold isostatically pressing the powder at a pressure of 350 MPa for 8 minutes to obtain an intermediate;
[0060] Step A2: in an environment where the vacuum degree is less than or equal to 10 Pa, the temperature is raised to 600° C. at a heating rate of 1° C. / min and then the temperature is kept. After keeping the temperature for 10 minutes, pressurization is started, and the pressure is pressed to 40 MPa, followed by keeping the temperature and pressure for 120 minutes. After the heat and pressure are completed, the temperature is lowered to room temperature and the pressure is lowered to normal pressure to complete vacuum hot pressing to obtain a ZMO green billet;
[0061] Step A3: Place the ZMO blank obtained in step A2 in an air atmosphere, first heat it to 600°C at a heating rate of 2.0°C / min, then heat it to 1150°C at a heating rate of 1°C / min, and then heat it to 1450°C at a heating rate of 1.5°C / min, keep it warm for 10 hours, and finally cool it to room temperature at a cooling rate of 2°C / min to complete sintering and obtain a ZMO target.
[0062] Example 4
[0063] The method is substantially the same as Example 1, except that the same mass of manganese trioxide is used to replace tantalum pentoxide.
[0064] Example 5
[0065] The method is substantially the same as Example 1, except that the same mass of titanium dioxide is used to replace tantalum pentoxide.
[0066] Example 6
[0067] The method is substantially the same as Example 1, except that a mixture of manganese trioxide and tantalum pentoxide of the same mass is used to replace tantalum pentoxide, and the mass ratio of manganese trioxide to tantalum pentoxide in the mixture is 1:1.
[0068] Example 7
[0069] The method is substantially the same as Example 1, except that a mixture of titanium dioxide and tantalum pentoxide of the same mass is used to replace tantalum pentoxide, and the mass ratio of titanium dioxide to tantalum pentoxide in the mixture is 1:1.
[0070] Example 8
[0071] The method is basically the same as Example 1, except that step A3 is specifically as follows: placing the ZMO blank obtained in step A2 in an air atmosphere, first heating it to 500°C at a heating rate of 0.5°C / min, then heating it to 1100°C at a heating rate of 0.8°C / min, and then heating it to 1380°C at a heating rate of 1.2°C / min, keeping the temperature for 8h, and finally cooling it to room temperature at a cooling rate of 1.5°C / min to complete sintering and obtain a ZMO target.
[0072] Example 9
[0073] The method is basically the same as Example 1, except that step A3 is specifically as follows: placing the ZMO blank obtained in step A2 in an air atmosphere, first heating it to 500°C at a heating rate of 1.5°C / min, then heating it to 1100°C at a heating rate of 0.8°C / min, and then heating it to 1550°C at a heating rate of 1.2°C / min, keeping the temperature for 8h, and finally cooling it to room temperature at a cooling rate of 1.5°C / min to complete sintering and obtain a ZMO target.
[0074] Comparative Example 1
[0075] The method is substantially the same as Example 1, except that tantalum pentoxide is replaced with tin dioxide of the same mass.
[0076] Comparative Example 2
[0077] The method is basically the same as Example 1, except that gallium trioxide of the same mass is used to replace tantalum pentoxide.
[0078] Comparative Example 3
[0079] The method is basically the same as Example 1, except that the same mass of aluminum oxide is used to replace tantalum pentoxide.
[0080] Performance Testing
[0081] The resistivity of the target material was tested using the four-point probe method;
[0082] The relative density of the target material is tested using the Archimedes drainage method;
[0083] The test methods for resistivity and relative density are shown in Table 1:
[0084] Table 1
[0085]
[0086] Result analysis:
[0087] 1. It can be seen from Examples 1-3 that when the process parameters in the preparation process of the ZMO target are slightly adjusted, although the resistivity and relative density of Examples 1-3 fluctuate, the overall fluctuation range is relatively small;
[0088] 2. It can be seen from Examples 1 and 4-5 that when other metal oxides are used instead of tantalum pentoxide, the resistivity of Examples 4-5 shows a certain upward trend relative to Example 1, which shows that doping tantalum pentoxide has a more significant effect on improving the conductivity of the ZMO target.
[0089] Further observation of Examples 6-7 shows that when Examples 6 and 7 replace tantalum pentoxide with a mixture of manganese trioxide and tantalum pentoxide and a mixture of titanium dioxide and tantalum pentoxide, respectively, the resistivity of Examples 6 and 7 shows a significant downward trend relative to Examples 4 and 5. More surprisingly, the resistivity of any one of Examples 6-7 is even lower than that of Example 1. It can be seen that there is a certain synergistic effect between manganese trioxide and tantalum pentoxide, and between titanium dioxide and tantalum pentoxide, which further improves the conductivity of the target material.
[0090] At the same time, it can be seen from Example 6 that, in the comparison between Examples 4 and 5, the resistivity of the target material with ZMO added with manganese trioxide is higher than that of the target material with titanium dioxide added; but when manganese trioxide and tantalum pentoxide are used together in Example 6, the resistivity of Example 6 is lower than that of Example 7. It can be seen that the synergistic effect between manganese trioxide and tantalum pentoxide is more intense, and the improvement of the conductivity of the target material is more significant;
[0091] 3. It can be seen from Example 1 and Examples 8-9 that when the first stage heating rate or the third stage insulation temperature in step A3 is changed, the resistivity and relative density of Examples 8-9 both show a significant upward trend relative to Example 1. It can be seen that the process of Examples 8-9 is not conducive to the formation of a dense internal structure of the target material and the defects in the target material itself affect the carrier migration ability of the target material, thereby resulting in an increase in resistivity;
[0092] 4. It can be seen from Example 1 and Comparative Examples 1-3 that when other metal oxides are used to replace tantalum pentoxide, the conductivity of the target material shows a significant downward trend. It can be seen that not all metal oxides with conductivity can improve the conductivity of the ZMO target material.
[0093] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A ZMO target material, characterized in that: Made from zinc oxide, magnesium oxide and doped metal oxides; The doped metal oxide is selected from at least one of tantalum pentoxide, cerium dioxide, titanium dioxide, niobium pentoxide, manganese trioxide, and chromium trioxide; The mass ratio of the metal elements in the zinc oxide and magnesium oxide is 73-91:9-27; The metal elements in the doped metal oxide are 1000 to 10000 ppm of the total mass of the metal elements in the ZMO target.
2. The ZMO target according to claim 1, characterized in that: The doped metal oxide contains at least tantalum pentoxide.
3. The ZMO target according to claim 1, characterized in that: The doped metal oxide is a mixture of tantalum pentoxide and manganese trioxide, and the mass ratio of tantalum pentoxide to manganese trioxide is 1:
1.
4. A method for preparing the ZMO target material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: Mixing zinc oxide powder, magnesium oxide powder and doped metal oxide powder with pure water to obtain a slurry; Step 2: The slurry prepared in step 1 is spray granulated, cold isostatically pressed, vacuum hot pressed, and sintered to obtain a ZMO target.
5. The method for preparing a ZMO target according to claim 4, characterized in that: The step 1 specifically comprises: mixing zinc oxide powder, magnesium oxide powder and doped metal oxide powder with a dispersant, a binder and pure water to obtain a slurry; The added amount of the dispersant is 1 to 3% of the total mass of zinc oxide powder and magnesium oxide powder; The amount of the binder added is 1 to 3% of the total mass of the zinc oxide powder and the magnesium oxide powder; The dispersant is selected from any one of polyvinyl pyrrolidone and polycarboxylic acid; The binder is selected from any one of polyvinyl alcohol, carboxymethyl cellulose, polyacrylamide, polyacrylic acid salt and polyethylene glycol.
6. The method for preparing a ZMO target according to claim 4, characterized in that: The step 2 includes the following sub-steps: Step A1: spray granulating the slurry obtained in step 1 to obtain a powder, and then cold isostatically pressing the powder at a pressure of 250 to 350 MPa for 3 to 8 minutes to obtain an intermediate; Step A2: placing the intermediate obtained in step A1 in an environment with a vacuum degree of less than or equal to 10 Pa and performing vacuum hot pressing to obtain a ZMO green body; Step A3: sintering the ZMO green blank obtained in step A2 in an air atmosphere to obtain a ZMO target.
7. The method for preparing a ZMO target according to claim 6, characterized in that: The vacuum hot pressing specifically comprises: in an environment where the vacuum degree is less than or equal to 10Pa, heating the temperature to 400-600°C at a heating rate of 0.4-1°C / min and starting to keep the temperature, and starting to pressurize after keeping the temperature for 10-30min, and pressurizing to a pressure of 10-40MPa, and then keeping the temperature and pressure for 120-360min. After the heat preservation and pressure keeping are completed, the temperature is lowered to room temperature and the pressure is lowered to normal pressure to complete the vacuum hot pressing.
8. The method for preparing a ZMO target according to claim 6, characterized in that: In an air atmosphere, the temperature is first increased to 400-600°C at a heating rate of 1.0-2.0°C / min, then increased to 1050-1150°C at a heating rate of 0.5-1°C / min, and then increased to 1300-1450°C at a heating rate of 0.8-1.5°C / min, kept warm for 6-10 hours, and finally cooled to room temperature at a cooling rate of 1-2°C / min to complete sintering and obtain a ZMO target.
Citation Information
Patent Citations
Electrically conducting transparent film and its preparing process
CN101221830A
A zinc oxide magnesium target and its preparation method
CN114736013B
Cited By
Zinc oxide doped target material preparation method, target material, film preparation method and film
CN120117889A